The adrenal gland: between diagnostics and conservative or surgical therapy Die Nebenniere: zwischen Diagnostik, konservativer und operativer Therapie - Bergmann, Tanja (Journal für Urologie und Urogynäkologie, 2022)
The adrenal glands play a central role in the regulation of several functions in the body. Hydrocortisone is the most essential hormone in the body and is also produced in the adrenal glands. On the one hand, diseases of the adrenal glands can present with symptoms of hormonal overproduction or insufficiency. On the other hand, incidentally detected tumors of the adrenal glands can be a challenge not only for endocrinologists but also for other medical disciplines and require special diagnostic and therapeutic measures. The latest European guidelines provide good practical advice on the topic of adrenal incidentalomas. In many cases after completion of the diagnostic cascade, a multidisciplinary decision-making team is needed for planning of the definitive therapeutic algorithm.
CRIS-Team Scopus Importer:2022-12-09
Keywords: Adrenal adenoma; Adrenal carcinoma; Adrenal incidentaloma; Adrenalectomy; Hormonal activity